Analysing the Environmental Consequences of Urbanization on Climate Change in Kaduna State, Nigeria - Oyelami, S. M.; Idowu, T. M.; Akinremi, M. (Journal of Spatial Information Sciences, 2025)
The rapid urbanization experienced by many regions like Kaduna state, Nigeria, has become a major issue of concern due to its potential effects on the local climate. This research aimed to analyse the environmental consequences of urbanization on climate change in Kaduna State, Nigeria, from 2008 to 2023 to provide future projections of these consequences. This was done by analysing the spatio-temporal Land Use and Land Cover (LULC) changes in Kaduna, analysing the relationships between the LULC, Land Surface Temperature (LST) and Normalized Difference Built-Up index (NDBI) trends in the state, examining the correlation between LST and NDBI. Landsat imageries for 2008, 2013, 2018 & 2023 were used for determining the LULC, LST & NDBI over Kaduna state, precipitation, and relative humidity data from NASA’s POWER (Prediction of Worldwide Energy Resources).  The study leveraged the ability of Artificial Neural Network (ANN) and Cellular Automata (CA) within the Modules for Land Use Change Evaluation framework to model complex, non-linear relationships for prediction analysis. The model’s accuracy was measured using Kappa and had an accuracy level of 0.67. Some key findings include doubling the developed areas from 12.37% to 24.85% from 2008-2023 with a corresponding decrease in cultivated and rocky areas. A strong positive correlation was also identified between urbanization and land surface temperature within the study area, suggesting the presence of urban heat island effects. The projection for 2043 shows that urban growth would most likely continue with developed areas expected to reach 35.54% in 2043, precipitation and humidity are also likely to decline. The study provides valuable insights for urban planners and policymakers by emphasizing the need for sustainable urban development strategies and climate resilience measures within Kaduna state.
Keywords: Precipitation; Urbanization; Land surface temperature; Climate change